2021
DOI: 10.3390/cancers13081881
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Drift Association with Cancer Risk and Survival, and Modification by Sex

Abstract: To investigate age- and sex-specific DNA methylation alterations related to cancer risk and survival, we used matched case–control studies of colorectal (n = 835), gastric (n = 170), kidney (n = 143), lung (n = 332), prostate (n = 869) and urothelial (n = 428) cancers, and mature B-cell lymphoma (n = 438). Linear mixed-effects models were conducted to identify age-, sex- and age-by-sex-associated methylation markers using a discovery (controls)-replication (cases) strategy. Replication was further examined usi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 55 publications
(72 reference statements)
1
3
0
Order By: Relevance
“…Our study results on the relationship between HannumAge and cancer were consistent with Li et al, 2022 prospective cohort study, which revealed a strong dose-response relationship between epigenetic clock and cancer risk (29). Similarly, case-control study of lung cancer (n=332) reported a strong positive correlation (Beta=0.13, P<2.2×10 -16 ) between methylation and both age and lung cancer risk (30). In addition, a 2019 study demonstrated a significant correlation between standardized measurements of rapid epigenetic aging and cancer incidence (HR: 1.50, P=3.4×10 −3 ) (10).…”
Section: Discussionsupporting
confidence: 91%
“…Our study results on the relationship between HannumAge and cancer were consistent with Li et al, 2022 prospective cohort study, which revealed a strong dose-response relationship between epigenetic clock and cancer risk (29). Similarly, case-control study of lung cancer (n=332) reported a strong positive correlation (Beta=0.13, P<2.2×10 -16 ) between methylation and both age and lung cancer risk (30). In addition, a 2019 study demonstrated a significant correlation between standardized measurements of rapid epigenetic aging and cancer incidence (HR: 1.50, P=3.4×10 −3 ) (10).…”
Section: Discussionsupporting
confidence: 91%
“…All these findings indicated a potential role for TMEM49 in TC homeostasis. In addition, the methylation level of TMEM49 was also associated with waist circumference [ 32 ], survival of cancer overall [ 33 ], and chemotherapy in breast cancer patients [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, the protumorigenic and antitumorigenic attributes of ER and ER, respectively, have been acknowledged [134]. In summary, the fact that women tend to use more photoprotective cosmetic products on their skin and the biological structural differences between male and female skin layers should also be considered, but further studies are imperative to clarify the enigmatic involvement of the age axis [135,136].…”
Section: Atherosclerosismentioning
confidence: 99%